Safety and Growth Optimization of Lactic Acid Bacteria Isolated From Feedlot Cattle for Probiotic Formula Design - Aristimuño Ficoseco, Cecilia; Mansilla, Flavia I.; Maldonado, Natalia C.; Miranda, Hortencia; Fátima Nader-Macias, María E.; Vignolo, Graciela M. (Frontiers in Microbiology, 2018)
In view to eliminate the use of low-dose antibiotics in livestock production, the research for alternative additives has increased lately. This study examined the safety of 40 LAB (Lactic Acid Bacteria) isolated from bovine feedlot environment and selected previously as potential probiotics. A high prevalence of sensitivity to ampicillin (AMP, 100%), gentamicin (GEN, 96.3%), kanamycin (KAN, 96.3%), clindamycin (CLI, 85.2%), chloramphenicol (CHL, 92.6%) and streptomycin (STR, 88.9%), moderate and high erythromycin (ERY, 48%) and tetracycline (TET, 79%) resistance respectively, were recorded. Feedlot enterococci and pediococci displayed high resistance to CLI, ERY, GEN and TET (73%, 100%, 54.5% and 73%, respectively). Seven of the fifteen investigated resistance genes were detected in lactobacilli, their presence not being always correlated with phenotypic resistance. Among STR resistance genes, aadA and ant(6) in 7.4% and 3.7% of isolates, respectively were observed; genes determining resistance to aminoglycosides, such as bla (7.4%), and aph(3”)-III (3.7%) were also identified. In addition, resistance cat and tetS genes (3.7% and 7.4%, respectively) were harbored by lactobacilli strains. The presence of ermB gene in 22.3% of isolates, including two of six strains found to be resistant to ERY, exhibited the highest prevalence among the assessed antibiotics. None of the feedlot lactobacilli harbored virulence factors genes, while positive PCR amplification for ace, agg, fsrA and atpA genes was found for enterococci. In view to produce large cell biomass for probiotic delivery, optimization growth conditions showed Mlac and Mgl media without peptone as optimal. L. acidophilus CRL2074, L. amylovorus CRL2115, L. mucosae CRL2069 and L. rhamnosus CRL2084 were selected as free of antibiotic resistance and virulence determinants strains, able to reach high cell numbers in non-expensive culture media and being compatible among them.